Desaturation - distance ratio: a new concept for a functional assessment of interstitial lung diseases (Clinics, 2010)
INTRODUCTION: The functional evaluation has become increasingly important in the understanding and management of patients with interstitial lung diseases. The cardiopulmonary exercise test and the six-minute walk test (6MWT), through their isolated variables, have been used to do this evaluation, with some limitations. OBJECTIVES: We proposed a new composite index (desaturation distance ratio using continuous peripheral oxygen saturation (SpO2) and the distance walked as a more reliable tool for doing a functional evaluation of these patients. METHODS: 6MWT was performed by interstitial lung diseases patients and controls. Analyzed parameters were walked distance and desaturation area (DAO2), obtained by taking the difference between maximal SpO2 possible (100%) and patient's SpO2 every 2 seconds. desaturation distance ratio was calculated using the ratio between DAO2 and distance walked. RESULTS: Forty-nine interstitial lung diseases patients and 11 control subjects completed the protocol. The mean (SD) age was 60 (12) years and 65 (9) years, respectively (p:NS). Data obtained from 6MWT showed a significant statistical difference between interstitial lung diseases patients and controls: mean walked distance (430 and 602 meters, respectively); SpO2 minimal maintained at least 10 seconds - SpO2 min (85% and 94%, respectively), and median desaturation distance ratio (10 and 2.5, respectively). A correlation analysis, considering interstitial lung diseases patients, revealed the best correlation between desaturation distance ratio and DLco (r= - 0.72; p